Uncovering what lies beneath a Salmonella enterica empyema. (2nd September 2015) - Woo, Jia Wei; Tam, John Kit Chung; Chan, Douglas Su Gin; Wang, Shi; Ying, Lee Shir
Abstract : A 67-year-old woman with myelodysplastic syndrome (MDS) and transfusional haemosiderosis developed Salmonella empyema caused by direct extension from splenic abscesses. She was successfully treated with antibiotics, pleural decortication and splenectomy. She had presented with fever after being treated for presumed pneumonia and parapneumonic effusion 2 months prior. CT scan showed splenic abscesses eroding through the diaphragm causing a left pleural empyema. Pleural fluid and spleen bacterial cultures grew Salmonella enterica . She was treated with 4 weeks of antibiotics and underwent surgical pleural decortication and splenectomy in the same sitting. She made a good postoperative recovery. Patients with severe iron overload are susceptible to various types of bacterial sepsis, including salmonellosis. It is unusual for enteric bacterial such as Salmonella to present with empyema, and should prompt a search for intra-abdominal infection. Pleural decortication and splenectomy can be performed during the same surgical sitting and can lead to good surgical outcomes.